Chemotherapeutic Potential of Epimedium brevicornum Extract: The cGMP-Specific PDE5 Inhibitor as Anti-Infertility Agent Following Long-Term Administration of Tramadol in Male Rats - Ahmed S. Abdelaziz; Mohamed A. Kamel; Amany I. Ahmed; Shimaa I. Shalaby; Salama M. El-darier; Amany Magdy Beshbishy; Gaber El-Saber Batiha; Suliman Y. Alomar; Dina M. Khodeer (Antibiotics, 2020)
Epimedium brevicornum Maxim (EbM) is a well-known Chinese herb that has been widely used for the treatment of several diseases. The main purpose of this study is to examine the role of Epimedium brevicornum extract in certain andrological parameters in rats as a natural modulator for adverse viewpoints associated with chronic administration of tramadol (TAM). Fifty rats were categorized into five groups. Untreated rats were known as Group I, whereas rats in Groups II and III were administered 2.43 g/kg/day of E. brevicornum extract and 50 mg/kg/day of TAM for 130 consecutive days, respectively. Both of Groups IV and V were administered TAM for 65 successive days, followed by concomitant use of both drugs for another 65 days, with the E. brevicornum extract at doses of 0.81 and 2.43 g/kg/day, respectively. TAM showed an injurious effect on sperm attributes, serum hormones, tissue malondialdehyde, superoxide dismutase, and nitric oxide. Elevation of the apoptotic marker Bax and a reduction of Bcl2 were recorded. Histopathological abnormalities have been reported in rat testicles. Rats treated with E. brevicornum extract with TAM showed an improvement in all the parameters tested. It could be presumed that E. brevicornum extract plus TAM exhibits a promising effect on the enhancement of male anti-infertility effects.